2017
DOI: 10.3766/jaaa.16044
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Hearing Loss, Postural Control, and Mobility in Older Adults: A Systematic Review

Abstract: There is evidence for the independent relationship between HL and objective measures of postural control in the elderly. However, a more comprehensive understanding of the mechanisms underlying this relationship is yet to be elucidated. Concurrent diagnosis, treatment, and rehabilitation of these two modalities may reduce falls and increase QoL in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 69 publications
5
76
1
2
Order By: Relevance
“…These results coincide with the mixed literature regarding hearing loss and balance difficulty among older adults, as well as whether hearing aids improve balance for older adults with hearing loss [ 23 ]. Older adults with hearing loss have been shown to have increased sway compared to older adults with normal hearing, and hearing aids have been shown to improve static balance and balance outcome measures such as the Berg Balance Scale (BBS) [ 12 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…These results coincide with the mixed literature regarding hearing loss and balance difficulty among older adults, as well as whether hearing aids improve balance for older adults with hearing loss [ 23 ]. Older adults with hearing loss have been shown to have increased sway compared to older adults with normal hearing, and hearing aids have been shown to improve static balance and balance outcome measures such as the Berg Balance Scale (BBS) [ 12 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the existing literature, hearing impairment was identified as a significant risk factor for falls in homebound community‐dwelling older adults (Agmon, Lavie, & Doumas, ; Wilson, Garner, & Loprinzi, ). Hearing impairment often negatively impacts postural control and balance, which can further cause falls in the older adults (Agmon et al, ). Assessing older adults’ hearing function and assisting older adults with hearing impairment may help prevent falls in the homebound older adult population.…”
Section: Discussionsupporting
confidence: 71%
“…In the further adjusted variable model, hearing loss (moderate) was still a risk factor for falls. A previous systematic review study found a significant association between hearing loss and falls [37]. Meanwhile, in a survey of adults by Elizabeth R. Heitz, it was suggested that hearing loss may be a clinical indicator of increased fall risk [16].…”
Section: Discussionmentioning
confidence: 99%